On the way of classifying new states of active matter. (1st July 2016) - Menzel, Andreas M
Abstract: With ongoing research into the collective behavior of self-propelled particles, new states of active matter are revealed. Some of them are entirely based on the non-equilibrium character and do not have an immediate equilibrium counterpart. In their recent work, Romanczuk et al (2016 New J. Phys. 18 063015 ) concentrate on the characterization of smectic-like states of active matter. A new type, referred to by the authors as smectic P, is described. In this state, the active particles form stacked layers and self-propel along them. Identifying and classifying states and phases of non-equilibrium matter, including the transitions between them, is an up-to-date effort that will certainly extend for a longer period into the future.